UPAYA MENINGKATKAN HASIL BELAJAR BIOLOGI SISWA MELALUI PENDEKATAN KONTEKSTUAL DENGAN MEDIA POWERPOINT - Jhonas Dongoran (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2019)
This study aims to determine whether learning through a contextual approach with PowerPoint media can improve student biology learning outcomes on the subject of the Ecosystem. The study was conducted at Sibabangun Public High School 1. The population in this study were all senior students X SMA 1 Sibabangun which consisted of 3 classes. From the population a sample of 2 classes was determined, namely the experimental class and the control class. Both classes were given different treatment, the experimental class was given teaching through a contextual approach with PowerPoint media, while the control class was given teaching through the lecture method. From the data analysis for the experimental class, post-tests were obtained (83.56 ± 7.54). In the control class, post-test was obtained (68.93 ± 7.82). Both data are normally distributed. From the hypothesis testing obtained thitung = 3.419 and at the significance level α = 0.05 with dk = 58 obtained t table = 1.574. Because tcount> ttable then tcount is in the reception area Ha. This means that learning through a contextual approach with PowerPoint media is better than learning through the lecture method. Learning through contextual approaches with PowerPoint media can improve student biology learning outcomes by 60.31%. Keywords: Learning Outcomes, Contextual, PowerPoint